High burden and seasonal variation of paediatric scabies and pyoderma prevalence in The Gambia: A cross-sectional study - Armitage, Edwin P.; Senghore, Elina; Darboe, Saffiatou; Barry, Momodou; Camara, Janko; Bah, Sulayman; Marks, Michael; Cerami, Carla; Roca, Anna; Antonio, Martin; Turner, Claire E.; de Silva, Thushan I. (PLOS Neglected Tropical Diseases, 2019)
Background Scabies is a WHO neglected tropical disease common in children in low- and middle-income countries. Excoriation of scabies lesions can lead to secondary pyoderma infection, most commonly by Staphyloccocus aureus and Streptococcus pyogenes (group A streptococcus, GAS), with the latter linked to acute post-streptococcal glomerulonephritis (APSGN) and potentially rheumatic heart disease (RHD). There is a paucity of data on the prevalence of these skin infections and their bacterial aetiology from Africa. Methodology/Principal findings A cross-sectional study, conducted over a four-month period that included the dry and rainy season, was conducted to determine the prevalence of common skin infections in Sukuta, a peri-urban settlement in western Gambia, in children <5 years. Swabs from pyoderma lesions were cultured for S. aureus and GAS. Of 1441 children examined, 15.9% had scabies (95% CI 12.2–20.4), 17.4% had pyoderma (95% CI 10.4–27.7) and 9.7% had fungal infections (95% CI 6.6–14.0). Scabies was significantly associated with pyoderma (aOR 2.74, 95% CI 1.61–4.67). Of 250 pyoderma swabs, 80.8% were culture-positive for S. aureus, and 50.8% for GAS. Participants examined after the first rains were significantly more likely to have pyoderma than those examined before (aRR 2.42, 95% CI 1.38–4.23), whereas no difference in scabies prevalence was seen (aRR 1.08, 95% CI 0.70–1.67). Swab positivity was not affected by the season. Conclusions/Significance High prevalence of scabies and pyoderma were observed. Pyoderma increased significantly during the rainy season. Given the high prevalence of GAS pyoderma among children, further research on the association with RHD in West Africa is warranted.